Pruni cortex ameliorates skin inflammation possibly through HMGB1-NFκB pathway in house dust mite induced atopic dermatitis NC/Nga transgenic mice - Watanabe, Kenichi (J Clin Biochem Nutr, 2015)
Pruni cortex, the bark of Prunus jamasakura Siebold ex Koidzumi, has been used in the Japanese systems of medicine for many years for its anti-inflammatory, antioxidant and antitussive properties. In this study, we investigated the effect of pruni cortex on atopic dermatitis NC/Nga mouse model. Atopic dermatitis-like lesion was induced by the application of house dust mite extract to the dorsal skin. After induction of atopic dermatitis, pruni cortex aqueous extract (1 g/kg, p.o.) was administered daily for 2 weeks. We evaluated dermatitis severity, histopathological changes and cellular protein expression by Western blotting for nuclear and cytoplasmic high mobility group box 1, receptor for advanced glycation end products, nuclear factor κB, apoptosis and inflammatory markers in the skin of atopic dermatitis mice. The clinical observation confirmed that the dermatitis score was significantly lower when treated with pruni cortex than in the atopic dermatitis group. Similarly pruni cortex inhibited hypertrophy and infiltration of inflammatory cells as identified by histopathology. In addition, pruni cortex significantly inhibited the protein expression of cytoplasmic high mobility group box 1, receptor for advanced glycation end products, nuclear p-nuclear factor kappa B, apoptosis and inflammatory markers. These results indicate that pruni cortex may have therapeutic potential in the treatment of atopic dermatitis by attenuating high mobility group box 1 and inflammation possibly through the nuclear factor κB pathway.